IMPLEMENTASI AGENDA WOMEN, PEACE AND SECURITY DI INDONESIA PADA SITUASI PANDEMI GLOBAL COVID-19 - Ayusia Sabhita Kusuma (Indonesian Journal of International Relations, 2022)
This article elaborates the responses and challenges of implementing the WPS agenda in Indonesia in the context of the Covid-19 pandemic. These responses and challenges are seen through the four pillars of WPS, namely Prevention, Participation, Protection, and Assistance and recovery. This article using descriptive qualitative method and using concept of Women, Peace and Security. The findings are in the Prevention and Protection pillar, there has a mechanism for collecting data on gender-based violence by government institutions, as well as protocols for handling the pandemic. In the pillars of participation, assistance and recovery, there has been an increase of participation of women’s groups and civil society organizations in policy-making related to WPS, as well as assistance and handling of the pandemic. However, the mechanisms have not specifically and effectively targeted affected women in conflict areas in Indonesia. WPS RAN has not become a reference in handling pandemic.